Applying Video Hero Modelling and Praising to Transition-related Behaviours 'Needing Development' Exhibited by Students with Down Syndrome: A Preliminary Investigation - Ohtake, Yoshihisa; Hatano, Mika (International journal of disability, development, and education, 2018)
The present study examined the effectiveness of video hero modelling and praising (VHMP), which has been proved as effective in behaviour change for students with autism spectrum disorders (ASD), in improving the transition-related behaviours of two elementary-aged students with Down Syndrome (DS). Each participant watched a video in which she exhibited appropriate transition-related behaviours side by side with her hero in the setting where the target behaviours were expected to occur. In addition, the hero praised the student for exhibiting the target behaviours in the video. A multiple-baseline-across-settings design was utilised for one student and an AB design for the other to determine if VHMP contributed to their behaviour change. Results showed that their transition-related behaviours dramatically improved immediately after VHMP was introduced. These findings imply that VHMP can be applied to behaviour change not only for students with ASD but also for those with DS.